Higher Ring Derivation and Intuitionistic Fuzzy Stability - Ick-Soon Chang (Abstract and Applied Analysis)
We take account of the stability of higher ring derivation in intuitionistic fuzzy Banach algebra associated to the Jensen type functional equation. In addition, we deal with the superstability of higher ring derivation in intuitionistic fuzzy Banach algebra with unit.